Case Studies on Conservation and Seismic Strengthening/Retrofitting of Existing Structures 2020
DOI: 10.2749/cs002.021
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Strengthening of a Characteristic Reinforced Concrete Building in Patras, Greece

Abstract: <p>The design and application of strengthening measures aiming to effectively counter possible weaknesses related to the extensive architectural modification of a characteristic reinforced concrete building is discussed in this chapter. Several balconies were removed as part of the architectural interventions. Externally bonded reinforcement consisting of steel and fibre reinforced polymer laminates was applied as an “answer” to possible changes in flexural stress of selected structural elements in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In the literature, there are various analytical procedures proposed to determine the increase of ductility. The current paper is a continuation of previous research works [1], [2] that proposes a further analytical formulation for calculating the ductility factor after the confinement of RC columns with FRP sheets. In addition to the proposed analytical relationship, the comparison includes respective equations that are proposed in the previous and in the current draft version of Eurocode 8part 3 (EC8-3), along with similar equations proposed in the previous and the revised version of the Greek Code for Structural Interventions.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the literature, there are various analytical procedures proposed to determine the increase of ductility. The current paper is a continuation of previous research works [1], [2] that proposes a further analytical formulation for calculating the ductility factor after the confinement of RC columns with FRP sheets. In addition to the proposed analytical relationship, the comparison includes respective equations that are proposed in the previous and in the current draft version of Eurocode 8part 3 (EC8-3), along with similar equations proposed in the previous and the revised version of the Greek Code for Structural Interventions.…”
Section: Introductionmentioning
confidence: 84%
“…In many cases of severely damaged buildings, the lack of ductility, particularly in primary seismic columns, was found out to be a very crucial parameter that leads failure to develop into total/fatal collapse. Therefore, the enhancement of ductility in columns could serve also as a strengthening and/or retrofitting strategy to improve the seismic behaviour of existing RC buildings, protecting the lives of its residents [1].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the existing structures in earthquake prone areas need to be strengthened either because they have been damaged in previous earthquakes or because they have been designed without or with old code provisions. The use of additional Reinforced Concrete (RC) layers or jackets has been proved to be an effective technique and there are various published studies in this field [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These studies highlight the effectiveness of the use of additional RC elements and it has been found that two important parameters which affect the performance of this technique is the connection between the old and the new concrete and the shrinkage of the new concrete of the layer/jacket [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the above strength degradation effects, various repairing and strengthening procedures can be used for the seismic upgrading of existing RC buildings [8,[11][12]. Certainly this upgrading of Cultural Heritage structures must be realized by using materials and methods in the context of the sustainable structures [13].…”
Section: Introductionmentioning
confidence: 99%